IMPLANTATION OF POSTERIOR-CHAMBER PHAKIC INTRAOCULAR LENS pIOL-3 IN HIGH MYOPIA (preliminary report) - G. V. Sorokoletov; V. K. Zuev; E. R. Tumanyan; M. Z. Frankovska-Gerlak (Oftalʹmologiâ, 2015)
Aim. To assess preliminary clinical functional outcomes of phakic intraocular lens pIOL-3 implantation in high myopia.Patients and methods. pIOL-3 was implanted in 6 patients (10 eyes) aged 27‑63 with high myopia and no concomitant pathologies. Follow-up period varied from 1 to 12 months. IOL is made of hydrophilic material Contamac CI26 with water content of 26% and refraction index of 1.46. pIOL design (holes in the haptic portions) provides its matching to ciliary sulcus size (0.5 mmless than linear size of the sulcus). Preoperative and postoperative examination included visual acuity measurement, biomicroscopy, ophthalmoscopy, visual field test, tonometry, endothelial microscopy, and ultrasound biomicroscopy. Simplicity of surgical technique, adaptability of haptics, and postoperative course were evaluated.Results. Early postoperative period was uncomplicated. Uncorrected (UCVA) and best-corrected visual acuity (BCVA) improved in the first hours after the surgery. No visual acuity worsening (as compared with preoperative BCVA) was observed. Surgical procedure did not affected IOP even despite the absence of basal iridotomy. Maximum endothelial cell loss was less than 5%. No IOL forward «vaulting» was observed.Conclusions. pIOL implantation in high myopia patients is safe and provides maximum visual acuity in the first postoperative hours. Owing to its design this IOL can be implanted into ciliary sulcus (which size is0.5 mmless than IOL diameter) without forward «vaulting».